STRUCTURE OF THE ARCHAEOLOGICAL MAP FLOW REGIONS OF THE KASHKADARYA RIVER - Makhmudova Azizakhan Nasirovna (Western European Studies, 2024)
This article covers the archaeological research of the Kashkadarya oasis and the identification and mapping of archaeological monuments under the leadership of R.H.Suleymanov, along with the determination of the historical boundaries of the monuments, issues of their cultural affiliation, the construction of new irrigation systems and water reservoirs
Keywords: R.H. Suleymanov; irrigation system; monument